Optimization of Creative Learning Media Usage in the Teaching and Learning Process in Elementary Schools through Collaboration between PGSD Teachers and the Community - Muammar Rinaldi; Rudi Hermansyah Sitorus; Nur wahyuni; Irna Herliza Rizki; Muhammad Ranu Al Habib (Outline Publisher, 2023)
This study aims to optimize the use of creative learning media in the teaching and learning process in elementary schools through collaboration between PGSD teachers and the community. This community service program involves the development of media based on local wisdom and digital technology to improve the quality of learning. The research findings indicate that the collaboration between teachers, PGSD students, and the community has a positive impact on teachers' skills in using learning media, as well as enhancing student motivation and academic achievement. The community also plays a role in providing teaching materials and teaching aids relevant to local culture, enriching students' learning experiences. The evaluation shows improvements in learning outcomes and teacher satisfaction with the use of creative learning media. This program highlights the importance of community involvement in creating an inclusive, creative learning ecosystem based on local needs, and contributes to improving the quality of elementary education in Indonesia.